Impacts of climate change and climate variability on the spatio-temporal hydrological dynamics of Amazonia (2015)
The hydrological dynamics of the Amazon River basin are explored by studying the coupled water and energy balances within the Budyko Framework, using data of precipitation, runoff, actual and potential evapotranspiration in up to 146 sub-catchments. These are examined from the perspective of comparative hydrology, that its, regional patterns of hydrological quantities are used to design classification systems that consider the similarities between the catchments, revealing information about their co-evolution in terms of the underlying climatic, geological, ecological and landscape characteristics. An effort has been made towards diagnosing, understanding and modeling the hydrological variables at the sub-catchment scale, as well as predicting their fluctuations at the annual, interannual, the long-term time scale and the symmetry between them. For this reason, this dissertation contributes to update and strengthen evidences of natural climate variability, as well as possible signs of climate change in Amazonia.